On Runge approximation and Lipschitz stability for a finite-dimensional Schrödinger inverse problem - Rüland, Angkana; Sincich, Eva (Arxiv, 2020)
In this note we reprove the Lipschitz stability for the inverse problem for the Schr\"odinger operator with finite-dimensional potentials by using quantitative Runge approximation results. This provides a quantification of the Schr\"odinger version of the argument from Kohn and Vogelius in Comm. Pure Appl. Math. (1985) and presents a slight variant of the strategy considered by Alessandrini, de Hoop, Gaburro and Sincich in Asymptotic Analysis (2018) which may prove useful also in the context of more general operators.
Gesehen am 12.05.2021